EPIDEMIOLOGICAL, CLINICAL AND LABORATORY FEATURES OF IMPORTED MALARIA IN THE NORTH-WEST FEDERAL DISTRICT - K. E. Novak; E. V. Esaulenko; A. G. Dyachkov (Журнал инфектологии)
Purpose: analysis of epidemiological, clinical and laboratory features of imported malaria in the North-Western Federal district (NWFD) in 2012–2016. Research materials: the study included 84 patients treated for malaria in the hospitals of the NWFD. Results: 84 cases of malaria were registered in the NWFD from 2012 to 2016, which constituted 18,9% of all cases registered inRussian Federation(n=445):St. Petersburg(n=60),Arkhangelsk(n=10),Murmansk(n=5),Leningradregion (n=4),Vologdaregion (n=2) and 1 case in Komi,NovgorodandKaliningradregion. Patients with malaria had a history of a recent visit to: Asian countries (37%, n=31), West Africa (35%, n=30), North Africa (11%, n=7),South Africa(8%, n=7), East and Central Africa (3% correspondingly),Dominican Republic,CubaandSouth America(1% correspondingly). Pl. vivax was most common cause of malaria in patients visited Asia (87%), while recent travel to West Africa predispose patients to malaria caused by Pl. vivax in 37%, Pl. falciparum in 57% and Pl. оvale in 6% of all cases. All patients arrived from the North, South, Central Africa andDominican Republichad malaria caused by Pl. falciparum. Conclusion: in NWFD in 2012-2016 in the process of providing care to patients with malaria the following trends were marked: late referral of patients for medical care, careless collection of epidemiological data and travel history, late diagnosis of the disease, insufficient supply of antimalarial drugs and severe malaria in patients with comorbidity. Lack of adequate therapy with modern drugs has led to the lethal cases in patients with tropical malaria and the occurrence of late relapses of tertian malaria.